PENINGKATAN KEMAMPUAN BERBICARA ANAK MELALUI MEDIA CERITA BERGAMBAR (ANAK USIA 4-6 TAHUN) DI TK PANTI DHARMA KUMARA SANGGULAN KECAMATAN KEDIRI TAHUN 2020 - Purnama Dewi Luh Ayu; Sudarsana I Ketut; Budiasih Ni Wayan (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
Early childhood education is the most basic and most important education for a child. Through early childhood education, it is hoped that it will be able to stimulate six aspects of child development which consist of moral development, religion, social-emotional, physical motor, language, cognitive and artistic Of all these developments, interaction or communication is needed so that all developments can be stimulated, so the language skills of the children here are needed. The importance of language skills for early childhood can be developed through pictorial story media because here it will increase children's vocabulary and children's ability to express their fantasies in simple language. The problems that will be discussed include (1). How is the process of improving speaking skills through pictorial story media? (2). How to improve speaking skills through pictorial story media? (3). What efforts are made by the teacher to improve speaking skills through pictorial story media?. The theories used to analyze are Interaction theory, Audio Visual Memory (AVM) theory and Behaviorism theory. This research uses qualitative research. Data collection methods used were observation, interviews and document study. The collected data were analyzed using the qualitative descriptive analysis method with the steps of data reduction, data presentation and conclusion drawing. The results showed (1). The process of improving children's speaking skills through pictorial story media is carried out in two stages, namely planning and implementation. (2). Increasing children's speaking ability through pictorial story media can teach children to know and understand more vocabulary in an easier and more fun way. In storytelling, children can know new vocabulary and children can immediately see the situation of the story picture being read so that the child can understand the content of the story they are hearing. (3). The efforts made by the teacher to improve children's speaking skills through pictorial story media at TK Panti Dharma Kumara, namely providing effective stimulation to children, the teacher comes with enlightening language and choosing the right pictorial story media